2020
DOI: 10.3174/ajnr.a6582
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Carotid Lesions in Acute Ischemic Stroke: Mechanisms, Therapeutic Challenges, and Future Directions

Abstract: Approximately 15% of patients undergoing endovascular thrombectomy for anterior circulation acute ischemic stroke have a tandem lesion, defined as a severe stenosis or occlusion of the cervical internal carotid artery ipsilateral to its intracranial occlusion. Patients with tandem lesions have worse outcomes than patients with isolated intracranial occlusions, but the optimal management of their carotid lesions during endovascular thrombectomy remains controversial. The main options commonly used in current pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 63 publications
1
43
0
1
Order By: Relevance
“…disadvantages of carotid stent placement in the setting of EVT, [1][2][3] and the need for dual-antiplatelet therapy is often cited as an argument to forego emergent stent placement. Some authors even argue that emergent carotid endarterectomy might be a better alternative because it does not require dual antiplatelet therapy.…”
mentioning
confidence: 99%
“…disadvantages of carotid stent placement in the setting of EVT, [1][2][3] and the need for dual-antiplatelet therapy is often cited as an argument to forego emergent stent placement. Some authors even argue that emergent carotid endarterectomy might be a better alternative because it does not require dual antiplatelet therapy.…”
mentioning
confidence: 99%
“…Some authors considered stenting in TOs to be potentially hazardous, 25 while others tend to perform carotid artery stenting immediately after successful thrombectomy. 26 In a study recently reported by our group, we found that emergency stenting is safer in defined circumstances, including intraprocedural heparin avoidance, baseline ASPECTS > 8, and a straightforward MT with a first-pass complete recanalization. 27 In the present study, we confirmed the safety and efficacy of emergency stenting in TOs irrespective of ECL etiology, without differences in terms of sICH risk between the two groups.…”
Section: Emergency Stentingmentioning
confidence: 69%
“…Our hospital summed up the following points for attention in the course of treatment [1] . The diameter of the vascular matching stent should be selected, because there are many bends of the internal carotid artery, so using Navien guide tube can reduce the walking distance of stent combined with thrombus, reduce the risk of thrombus detachment and improve the efficiency of vascular recanalization [2] .…”
Section: Discussionmentioning
confidence: 99%
“…There are many treatment methods for vascular recanalization, including intravenous thrombolysis, arterial thrombolysis, and mechanical thrombectomy, but the clinical outcome of intravenous thrombolysis and arterial thrombolysis is not good. [1,2] In recent years, intra-arterial mechanical therapy has gradually sprung up, such as destroying the thrombus of the occlusive segment or causing the embolus to deform and rupture through the arterial approach with the help of interventional equipment (guidewire, catheter, stent, etc). If necessary, interventional equipment can be used to remove the thrombus from the intracranial occlusive segment to restore and recanalize the occluded intracranial vessels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation